2019
DOI: 10.1371/journal.pgen.1008028
|View full text |Cite
|
Sign up to set email alerts
|

Satellite DNA-containing gigantic introns in a unique gene expression program during Drosophila spermatogenesis

Abstract: Intron gigantism, where genes contain megabase-sized introns, is observed across species, yet little is known about its purpose or regulation. Here we identify a unique gene expression program utilized for the proper expression of genes with intron gigantism. We find that two Drosophila genes with intron gigantism, kl-3 and kl-5 , are transcribed in a spatiotemporal manner over the course of spermatocyte differentiation, which spans ~90 hours… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 94 publications
(84 reference statements)
12
77
0
Order By: Relevance
“…In summary, the absence of the Y--dot fusion, and a lack of conservation of location for most ancestral Y genes in the affinis subgroup indicates that genes moved away independently from the Y in this clade. Y genes in D. melanogaster can be gigantic, due to huge introns [30] and require unique gene expression programs [34]. Multiple independent translocations of ancestral Y genes suggest that the Y chromosome may have been smaller in obscura subgroup flies compared to D. melanogaster, which is consistent with karyotypic findings [23].…”
Section: Independent Y Gene Gain In D Affinis and D Aztecasupporting
confidence: 67%
“…In summary, the absence of the Y--dot fusion, and a lack of conservation of location for most ancestral Y genes in the affinis subgroup indicates that genes moved away independently from the Y in this clade. Y genes in D. melanogaster can be gigantic, due to huge introns [30] and require unique gene expression programs [34]. Multiple independent translocations of ancestral Y genes suggest that the Y chromosome may have been smaller in obscura subgroup flies compared to D. melanogaster, which is consistent with karyotypic findings [23].…”
Section: Independent Y Gene Gain In D Affinis and D Aztecasupporting
confidence: 67%
“…We observed poor expression of the Y in somatic cells, and increased expression in E1°, M1°, and L1° primary spermatocytes. This is likely to occur from expression of a few highly transcriptionally active Y-linked genes originally identified by the cytologically visible Y-chromosome loops present at these stages (64,65). The decrease in sex chromosome expression in M1° and L1° did not reflect an overall decrease in total gene expression compared to somatic lineages ( Fig.…”
Section: We Looked At the Dynamics Of Sex Chromosome Gene Expression mentioning
confidence: 88%
“…The nuclear interior, less densely stained for DAPI, is occupied by the transcriptionally active Y chromosome (64,65,67) (Fig. 4A).…”
Section: We Looked At the Dynamics Of Sex Chromosome Gene Expression mentioning
confidence: 99%
“…In our previous study, we analyzed the expression of the Y-linked axonemal dynein 150 genes kl-3 and kl-5 and showed that these two mRNAs localized to cytoplasmic granules in 151 late SCs (Fingerhut et al, 2019). Using single molecule RNA fluorescent in situ hybridization 152 (smFISH), we found that mRNAs for four testis-specific axonemal dynein heavy chain genes 153 (the Y-chromosome genes kl-2, kl-3, and kl-5, as well as the autosomal gene Dhc98D 154 colocalize together within RNP granules in the cytoplasm of late SCs, with each SC containing 156 several of these cytoplasmic granules ( Fig.…”
Section: Axonemal Dynein Heavy Chain Mrnas Colocalize In Rnp Granulesmentioning
confidence: 99%
“…and kl-5, as well as the testis-specific axonemal dynein intermediate chain Dic61B, are 125 transcribed in SCs (Fingerhut et al, 2019). However, axoneme elongation does not begin 126 until after meiosis, suggesting that these mRNAs may not be translated until later in 127 development.…”
mentioning
confidence: 99%